The transition of global order : legitimacy and contestation - Terhalle, Maximilian, 1974- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2015)
"Why do international orders lack systemic legitimacy? This study examines the developing relationship between the US and China and explores the ways in which these two global powers are transitioning to a new global order, albeit one with significant risks and uncertainties for governance and legitimacy. Terhalle argues that the financial crisis of 2008/09 established China as the key challenger to the United States amid a process of order transition. Subsequent disagreements between these two powers about the future shape of the global order's legitimacy have manifested themselves in their intense competition with regard to spheres of influence in East Asia and the environment and ideology-related aspects of the order. In positing a new theoretical framework for understanding order and legitimacy in International Relations, The Transition of Global Order offers a significant contribution to the debate around world politics and the new global order"--
Machine generated contents note: -- 1.Global Orders: Contestation and Transition2.Order Transition, Systemic Legitimacy and Institutionalization 3.Order Transition in a Hybrid Environment4.Order Transition, Common Culture and Exceptional Worldviews5.Order Transition and Effectiveness6.Renegotiating the Security-related Rules of Global Order7.Renegotiating the Environmental Rules of Global Order8.Renegotiating the Ideology-related Aspects of Global Order9.Conclusion: The Politics of Sovereignty and the Failure of the Global Governance Concept.
Includes bibliographical references (pages 233-264) and index.
Keywords: Global Financial Crisis, 2008-2009.; World politics -- 21st century; International relations; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Globalization; United States -- Relations -- China; China -- Relations -- United States